New Possibilities of Brown Bullhead (Ictalurus nebulosus) Farming - Vinginder, Csaba (Acta Agraria Debreceniensis, 2003)
The brown bullhead (Ictalurus nebulosus) has been settled in Europe at the end of Century XIX from North America. In Hungary it has been brought in 1902. The naturalization of this species was successful because the brown bullhead found adequate conditions for its life and reproduction in Hungary. But it was unsuccessful because lost its excellent growth.In inland water habitats-and that’s why also fishponds-extraordinarily multiplied, but because of its slight growth this species is undesirable for the native farmers. The brown bullhead is concurrent for domestic fish species, on the other hand its weight not more than 150-200 g. Occasionally it was exterminated, but multiplied again and again.In 1999 we placed out black bullhead offspring in a pool of a new intensive fish farm, in order to breed at least 300-350 g weight for the customers. The accidental trial was surprisingly successful. Consequently, the black bullhead prefers the artificial food, and produces excellent growth parameters and specific feed-live weight conversation ratio.On the 20th of September 1999 there was placed 23 300 pieces of brown bullhead offspring, with 28 g average weight and 625 kg gross weight. When we sold them on the 22nd of February 2000, the gross weight was 3387 and the live weight gain was 2735 kg. The gross weight of the feed was 3041,8 kg, and the feed-live weight conversation ratio was 1,11 kg/kg.Because of this successful trial the managers of the farm wanted to start systematic experiments to work out the details of the intensive farming of brown bullhead. We undertook to help to find the right place of the species in the Hungarian fish processing because of the increasing native and foreign demand.